2018
DOI: 10.1021/acs.analchem.8b00360
|View full text |Cite
|
Sign up to set email alerts
|

A Plasticizer-Free Miniaturized Optical Ion Sensing Platform with Ionophores and Silicon-Based Particles

Abstract: Nanoscale ionophore-based ion-selective optodes (nano-ISOs) are effective sensing tools for in situ and real time measurements of ion concentrations in biological and environmental samples. While searching for novel sensing materials, nano-ISOs free of plasticizers are particularly important for biological and environmental applications. This work described plasticizer-free nano-ISOs based on Si-containing particles including PEGylated organosilica nanoparticles, PDMS nanospheres, and SiO microspheres, with di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 39 publications
0
29
0
Order By: Relevance
“…The nano-optodes could share a similar sensing mechanism with polymer film-based bulk optodes where an increase of K + concentration ([K + ]) leads to the deprotonation of a pH indicator (H + chromoionophore) in the nanospheres [19][20][21]. For example, the group of Bakker, Michalska, Clark, Cash, and our own have reported such nano-optodes based on different materials including Pluronic F-127, lipid covered plasticizer nanodroplets, conducting polymers, organosilicas, and quantum dots [14,15,[22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…The nano-optodes could share a similar sensing mechanism with polymer film-based bulk optodes where an increase of K + concentration ([K + ]) leads to the deprotonation of a pH indicator (H + chromoionophore) in the nanospheres [19][20][21]. For example, the group of Bakker, Michalska, Clark, Cash, and our own have reported such nano-optodes based on different materials including Pluronic F-127, lipid covered plasticizer nanodroplets, conducting polymers, organosilicas, and quantum dots [14,15,[22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 73%
“…For the nano-optode to work, the SDs must be able to change their locations in response to the target ions. It was achieved here by attaching the SDs on the distal end of the amphiphilic poly (ethylene oxide) chains and anchored onto the organosilica nanospheres [29]. The performance of the resulting nano-optodes was investigated and the possibility of using the nano-optodes on Nylon filter paper was also demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, this structural support function should also work with other materials while maintaining the sensing mechanism as long as the material properties are similar. The fundamental mechanism of IBNS has been demonstrated in a wide range of supporting matrices and is not impacted [ 22 , 23 , 24 , 25 ], as others have demonstrated that it is possible to make sensors with only plasticizer [ 24 ], brush block copolymers [ 27 ], surfactant alone [ 23 ], and even SiO 2 nanoparticles [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The structural components of IBNS can be altered from the traditional plasticized PVC fabrications to fit a specific need without hindering the ion exchange mechanism [ 22 , 23 , 24 , 25 ]. For example, Balaconis et al described biodegradable nanosensors to detect sodium with polycaprolactone polymer and a citric acid ester plasticizer while maintaining IBNS character [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…30–32 The Stöber process has been widely adopted to prepare various silicon-based NPs. 33–36 However, nanoparticles directly obtained by the Stöber method usually have a large size distribution. More monodisperse silica particles could be obtained through the reverse microemulsion method where silica was grown in a water-in-oil system.…”
Section: Introductionmentioning
confidence: 99%